Understanding Catalysis of Phosphate-Transfer Reactions by the Large Ribozymes - Lonnberg T (WILEY-V C H VERLAG GMBH, 2022)
Large ribozymes are unique among catalytic RNA molecules in that their reactions involve intermolecular nucleophilic attack on an RNA phosphodiester linkage. Crystal structures of near-atomic resolution are now available for the group I and group II self-splicing introns and the RNA subunit of RNase P. The structural data agrees well with the earlier models proposed on the basis of biochemical studies and the evidence at hand suggests that all of the large ribozymes utilize a mechanism in which coordination of MgII ions reduces the negative charge on the scissile phosphodiester linkage, as well as assists both the nucleophilic attack and the departure of the leaving group.